Pension reform and wealth inequality: Evidence from Denmark - Torben M. Andersen; Joydeep Bhattacharya; Anna Grodecka-Messi; Katja Mann (Sveriges Riksbank, 2022)
A growing literature explores reasons for rising wealth inequality, but disregards the role of pension systems despite their well-understood infiuence on life-cycle saving. In theory and according to available evidence, both pay-as-you-go (PAYG) and fully-funded (FF) pension schemes crowd out voluntary retirement saving. They differ because aggregate savings decrease in the former but increase under the latter system. Unlike most nations, Denmark has seen a decline in wealth inequality in recent decades. This paper studies a calibrated life-cycle model of Denmark and employs unique registry data to argue that a Danish pension system transition, from a mostly PAYG to a dominant, mandated FF scheme, explains much of this decline.
Keywords: D31; E01; E21; H55; G51; J32; 330; Wealth inequality; pension systems; crowding out; life-cycle savings